The effects of skilled people`s EEG-based neurofeedback training on learning the air rifle shooting skill in novices - Hatami, F.; Tahmasbi, F.; Pasbani, H. (Journal of Sports and Motor Development and Learning, 2024)
Introduction: This study aimed to determine the effects of skilled people`s EEG-Based neurofeedback training on learning of the rifle shooting skills in novices.